Hypervascular retained product of conception: Characteristic magnetic resonance imaging and possible relationship to placental polyp and pseudoaneurysm. Issue 1 (13th October 2017) - Shiina, Yuji; Itagaki, Takatomo; Ohtake, Hiroya
Abstract: The cases of two patients who developed myometrial vascularization following dilatation and curettage are described. In case 1, pathological diagnosis was possible with the resected specimens. This patient had hypervascular retained products of conception (RPOC). In case 2, the natural course of this pathological condition was observed, confirming a process of regression during repeated withdrawal bleeding. The three principal magnetic resonance imaging (MRI) findings in these cases were: (i) presence of a remnant; (ii) breaking of the junctional zone in contact with the remnant; and (iii) vascularization/flow voids infiltrating into the myometrium from the broken junctional zone. These three MRI findings differed in degree and varied in combination in each case of RPOC. Uterine artery pseudoaneurysms have been reported as intrauterine vascularization after abortion or delivery with subsequent spontaneous regression. These reports may include cases of hypervascular RPOC.